Higher fuel and food prices: Impacts and responses for Mozambique - Arndt, Channing; Benfica, Rui; Maximiano, Nelson; Nucifora, Antonio M.D.; Thurlow, James (Wiley, 2008)
Rising world prices for fuel and food represent a negative terms‐of‐trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short‐run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer‐term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade‐offs between short‐run mitigation and long‐run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.